Development and Validation of a Forced Choice Scale to Measure Job-Related Discomfort Among Customer Service Representatives - Bernardin, H. John (Academy of Management Journal, 1987)
The article discusses methods of measuring job-related discomfort. The author notes a number of obstacles to obtaining an accurate measure of negative emotions related to job performance, including the deliberate distortion of responses by employees. According to the author, employees may respond to questionnaires with answers they feel are most desirable to employers. Also measured in the study were variables surrounding employee turnover, including employees? intentions to leave a job and measures of voluntary job termination.